Effects of alginate hydrocolloid film permeated with vicenin 2 on wound healing in streptozotocin-induced diabetics Sprague Dawley rats - Tan, Woan Sean (2019)
Wound healing impairment is one of the debilitating complications caused by diabetes mellitus (DM) which leads to morbidity and mortality. Previous preliminary report of our team has showed that Vicenin-2 (VCN-2) bioactive compound which possesses potent wound healing properties is identified from Moringa oleifera extract (MO). The general objective of this study is to determine the wound healing efficacy of VCN-2 hydrocolloid film on diabetic rats. Firstly, the cytotoxicity and medicinal effects of VCN-2 was investigated through in vitro studies. A new sodium alginate (SA) film formulation contained VCN-2 was then optimized and developed, the various physicochemical tests were conducted on the developed VCN-2 film. Subsequently, the VCN-2 film was then tested in streptozotocin (STZ) induced male Sprague Dawley rats. The diabetes induced rat models were subjected to wound infliction and topical treatment of SA hydrocolloid film with VCN-2 in respective doses (12.5, 25 and 50 μM) for 14 days. Finally, the animals were sacrificed for wound healing assessment. Results indicated that VCN-2 hydrocolloid film has significantly reduced the production of pro-inflammatory cytokines and mediators (IL-6, IL-1β, TNF-α, NF-κB, iNOS and COX-2), while enhancing the production of healing growth factors (VEGF and TGF-β) in wound samples. During diabetic wound healing, the VCN-2 hydrocolloid film had influence inflammation phase by suppressing pro-inflammatory cytokines and proliferation phase by inducing growth factor expression. It has ameliorated prolong inflammatory process and enhanced healing through VEGF and TGF-β pathways. Taken together, VCN-2 hydrocolloid film is a promising new treatment to enhance impaired wound healing in hyperglycemic condition which prompts further investigation.